Modulation of Inflammatory Responses and miRNA Expression in UPEC-Induced Orchitis: Therapeutic Potential of Ciprofloxacin and Doxycycline - Nasser, Dhilal Dhiaa; froushani, Meysam Abtahi; Razi, Mazdak (Journal of Neonatal Surgery, 2025)
This study investigates the molecular mechanisms involved in uropathogenic Escherichia coli (UPEC)-induced orchitis in male Wistar rats, with a particular focus on the expression of specific miRNAs and their potential modulation by antibiotics, ciprofloxacin (CIP) and doxycycline (DOX). Forty-two male rats were divided into control and UPECI-induced groups, with subgroups treated at different time points post-infection (24 h, 72h, and one-week). UPEC infection was introduced via epididymal tail injections, and tissue samples were collected for gene expression analysis. The study measured the expression levels of miR-155, miR-138, miR-124, and key inflammatory markers such as SHIP1, SOCS1, TNF-α, and IL-6. Total RNA was extracted from testicular tissues, and quantitative real-time PCR (qRT-PCR) was performed to assess mRNA levels. Results revealed that UPEC infection significantly altered the expression of the studied miRNAs, with upregulation of miR-155 and downregulation of miR-138 and miR-124. Antibiotic treatment with CIP and DOX reduced the inflammatory response, as evidenced by decreased levels of miR-155, SHIP1, SOCS1, TNF-α, and IL-6, and restored the expression of miR-138 and miR-124, particularly in the CIP-treated groups. These findings suggest that CIP and DOX not only inhibit bacterial growth but also modulate immune responses, providing potential therapeutic strategies for UPEC-induced male infertility. This study underscores the role of miRNAs in regulating testicular inflammation and highlights the importance of timely antibiotic intervention in mitigating reproductive damage associated with UPEC infections. Further research is needed to optimize treatment protocols and explore long-term fertility outcomes